The Essence of Science: Unraveling the Nature of Science as a System, Its Characteristics, To Ethical Dimensions and Wisdom - Vina Latifah; Anneu Rosyanti Suryana (Gunung Djati Conference Series, 2026)
The aim of this research is to explore in depth the essence of science through five main pillars: science as a structured system of knowledge, the characteristics of science, the functional goals of science, the distinction between knowledge and wisdom, and the integration of ethical dimensions in scientific development. The research method employed is qualitative-descriptive with a library research approach. Data were collected through documentation techniques of primary and secondary literature, which were then critically analyzed to construct a conceptual synthesis regarding the epistemological and axiological foundations of science. The research results indicate that science is a rational-empirical knowledge system characterized by objectivity, systematicity, and universality. Functionally, science aims to provide explanation, prediction, and control over phenomena. However, this study asserts that science is distinct from wisdom; science focuses on the realm of "know-how" (technical), while wisdom focuses on "know-why" (moral values). In conclusion, science is not value-free but must be grounded in ethical dimensions and moral responsibility to ensure that the progress of civilization remains aligned with human dignity and the public good.